Pemanfaatan Framework Laravel dalam Pengembangan Web Apresiasi Seni Rupa Mahasiswa - Ridlo, Muhammad Ainur; Fajrie, Nur; Santoso, Santoso (Universitas Bunda Mulia, 2026)
This research aims to develop and test the feasibility, and effectiveness of the RUPAKU Web (Ruang Apresiasi Seni Rupa Universitas Muria Kudus) as a digital platform for art appreciation. The development method uses Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects were 30 PGSD students at Muria Kudus University who took the Fine Arts Product Creation course. Product feasibility was assessed by material, media, and language experts. Practicality was assessed through student and lecturer questionnaires. Effectiveness was measured using a pretest-posttest design to assess changes in art appreciation. Expert validation results show that the product is very feasible with scores of 94.16% (material), 90% (media), and 90.83% (language). Practicality test results from students and lecturers reached 93.75% and 92.5%, respectively (very practical category). The effectiveness test using the Paired Sample T-Test showed a significant difference between pretest and posttest scores (Sig. 0.000 < 0.05) with an N-Gain Score of 0.82 (high category). The conclusion is that the RUPAKU Web is feasible, practical, and effective as a digital space for appreciating fine arts for PGSD students.